1982
DOI: 10.1063/1.329879
|View full text |Cite
|
Sign up to set email alerts
|

Defects in hydrogenated amorphous silicon-carbon alloy films prepared by glow discharge decomposition and sputtering

Abstract: Properties of hydrogenated amorphous silicon-carbon alloy (a-Si1−xCx :H) films prepared by radio frequency (rf) glow discharge decomposition and rf sputtering have been investigated by means of electron spin resonance (ESR), infrared absorption, optical absorption, and photoconductivity measurements. Although the number of C-H per C atom [C-H]/[C] is larger than that of Si-H per Si atom [Si-H]/[Si], the ESR spin density increases greatly with the C content. The increase in the density of dangling bonds may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(29 citation statements)
references
References 15 publications
1
28
0
Order By: Relevance
“…These observations are consistent with the quite generally reported strong increase of the defect density with x (see e.g. [5]). The studies of effusion and IR absorption have also suggested that it is solely the carbon content that determines the hydrogen content in the films.…”
Section: Film Preparation and Characterizationsupporting
confidence: 91%
See 1 more Smart Citation
“…These observations are consistent with the quite generally reported strong increase of the defect density with x (see e.g. [5]). The studies of effusion and IR absorption have also suggested that it is solely the carbon content that determines the hydrogen content in the films.…”
Section: Film Preparation and Characterizationsupporting
confidence: 91%
“…Alloying of silicon with carbon is known to widen the energy gap. Unfortunately this is accompanied by a degradation of electronic properties such as photoconductivity, photoluminescence efficiency, which is due to the creation of additional defects [5,61. This tendency for defect creation might arise from differences in bond length, the tendency of C atoms for threefold coordination, or the incorportation of hydrogen in the film.…”
Section: Introductionmentioning
confidence: 99%
“…46 we have plotted pzN, versus x for three series of films. Curve a is due t o Morimoto et al [54] who measured the defect density by ESR, curve b from photoconductivity and PDS data published by Bullot et al. [161] and Boulitrop et al [23], and curve c from the paper of Fiorini et al [78].…”
Section: 21mentioning
confidence: 99%
“…a-Si photovoltaic technology has since advanced by taking advantage of a range of band gaps accessible through alloying with germanium or carbon 4,5 . Alloying of a-Si has led to multi-junction solar cells with somewhat higher efficiencies, but it also causes reduced electrical performance due to higher defect densities 6,7 . The poor conductivity and the limited bandgap range of a-Si alloys severely hinder the widespread applications of a-Si alloys despite their potential advantages of lower cost and ability to deposit on flexible substrates.…”
Section: Introductionmentioning
confidence: 99%